A trio family study showing association of the lymphotoxin-alpha N26 (804A) allele with coronary artery disease. - Consortium, P (2004)
Family-based studies to map susceptibility genes through linkage disequilibrium have been successful in early-onset diseases where parental-proband trios are readily collected, but are believed to be unworkable for late-onset diseases such as coronary artery disease (CAD). PROCARDIS is a European multicentre study that was designed to identify susceptibility genes for CAD. We have tested the transmission of a putatively functional allele, lymphotoxin-alpha N26 (804A), in more than 400 PROCARDIS trio families. The present study demonstrates association of this allele with CAD in white Europeans, a different ethnic group with a heavier CAD burden than the Japanese in which the association was initially identified, which suggests a broad relevance to CAD susceptibility. The practicalities of implementing a trio-family design for late-onset diseases are discussed.